2009
DOI: 10.1080/09593330903233901
|View full text |Cite
|
Sign up to set email alerts
|

Pilot scale investigation of zinc and sulphate removal from industrial discharges by biological sulphate reduction with molasses as electron donor

Abstract: A biological sulphate reduction process, with molasses as an electron donor, was used for the removal of zinc and sulphate from Rayon industrial wastewater. The process involved reduction of sulphate to sulphide under anaerobic conditions. The sulphide-rich effluent was used to remove zinc as zinc sulphide precipitate. The investigation was conducted at pilot scale with real wastewater from the Rayon industry as feed. The effects of sulphate loading rate and temperature of feeding wastewater were evaluated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The large and middle level viscose and rayon industries generally use 10–20 g/L of ZnSO 4 in acid bath of spinning process and generate 5–50 mass% of zinc in waste effluent . The concentration of zinc in Rayon industrial waste water of Angthog Province of Thailand is reported in the range of 110–300 mg/L whereas as 85 mg/L of zinc is reported from Baroda Rayon in India .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large and middle level viscose and rayon industries generally use 10–20 g/L of ZnSO 4 in acid bath of spinning process and generate 5–50 mass% of zinc in waste effluent . The concentration of zinc in Rayon industrial waste water of Angthog Province of Thailand is reported in the range of 110–300 mg/L whereas as 85 mg/L of zinc is reported from Baroda Rayon in India .…”
Section: Introductionmentioning
confidence: 99%
“…The techniques conventionally used by viscose industries for zinc removal include precipitation with lime/caustic soda and sulfate that requires large quantities of these chemicals and generate a bulk of toxic sludge which further requires expensive procedure for disposal . Other methods such as evaporation, solvent extraction, ion exchange, membrane filtration are both energy and cost intensive .…”
Section: Introductionmentioning
confidence: 99%